Using Review Words for teaching vocabulary in collage - Haris Dibdyaningsih (Universitas PGRI Madiun, 2019)
Review words is type of vocabulary building which is the easiest way to checking how is the students’ understanding dealing with the previous vocabulary given, especially for college students. Classroom observation research was used as the method in this study. The method is divided into some stages namely review, reduce, recycle, vocab college, role reversal, word soup, and vocab box. It is a method of straightly observing teaching process, which the observer taking notes, and/or coding instructional performances in the classroom or from recorded activities or lesson. It is going to define some steps that we need to apply the review words. Moreover, it is still important to upgrading collage students’ vocabulary because English as EFL will be very difficult term to reach when they are not seriously concern about the vocabulary. This paper will discuss the importance of using review words in checking students understanding in the certain level of English skill.